Measurement of the top quark charge in pp collisions at s√=7s=7 TeV with the ATLAS detector - Aad, G. (2013)
A measurement of the top quark electric charge is carried out in the ATLAS experiment at the Large Hadron Collider using 2.05 fb−1 of data at a centre-of-mass energy of 7 TeV. In units of the elementary electric charge, the top quark charge is determined to be 0.64 ± 0.02 (stat.) ± 0.08 (syst.) from the charges of the top quark decay products in single lepton tt¯tt¯ candidate events. This excludes models that propose a heavy quark of electric charge −4/3, instead of the Standard Model top quark, with a significance of more than 8σ.